Pengenalan Produk Olahan Tanaman Kangkung dan Pelestarian Kampung Wisata Kelurahan Sumber Rejo Balikpapan Tengah - Barokatun Hasanah; Lusi Ernawati; Ahmad Nizar; Ganang Bimantara; Erlingga Primashudi (Future Science, 2022)
The use of local vegetable gardens for tourism is growing quickly right now, offering not just stunning views but also other interesting experiences. Education tourism is one that is currently growing. For students, educational tourism can offer a learning experience outside of classes so that it can be used as a means of interacting and mingling with the community. Land kale Garden, which is located in the SumberRejo Village, Central Balikpapan, is one of the vegetable gardens that serves as a transportation for tourist communities. This region is highly interesting because it has a large amount of farming land kale. The name of land kale garden is derived from the occupation of the locals, who make up roughly 95% of their incomes as farmers who tend to and manage their own crops. It is necessary to carry out service community program activities for the making of land kale processed products and the preservation of tourist villages that are beneficial to the community in order to explore the potential area by taking a look at the opportunities or potential aspects. Through this community service activity, processed land kale products into brownies with the concept of using green vegetables and the development of garden tourism villages are well received and used as media for community activities as educational tours and increase skills in making brownies made from land kale.